Tools for measuring medical internship experience: a scoping review - Yingxi Zhao; Peris Musitia; Mwanamvua Boga; David Gathara; Catia Nicodemo; Mike English (BMC, 2021)
Abstract Background Appropriate and well-resourced medical internship training is important to ensure psychological health and well-being of doctors in training and also to recruit and retain these doctors. However, most reviews focused on clinical competency of medical interns instead of the non-clinical aspects of training. In this scoping review, we aim to review what tools exist to measure medical internship experience and summarize the major domains assessed. Method The authors searched MEDLINE, Embase, PsycINFO, ERIC, and the Cochrane Library for peer-reviewed studies that provided quantitative data on medical intern's (house officer, foundation year doctor, etc.) internship experience and published between 2000 and 2019. Three reviewers screened studies for eligibility with inclusion criteria. Data including tools used, key themes examined, and psychometric properties within the study population were charted, collated, and summarized. Tools that were used in multiple studies, and tools with internal validity or reliability assessed directed in their intern population were reported. Results The authors identified 92 studies that were included in the analysis. The majority of studies were conducted in the US (n = 30, 32.6%) and the UK (n = 20, 21.7%), and only 14 studies (15.2%) were conducted in low- and middle-income countries. Major themes examined for internship experience included well-being, educational environment, and work condition and environment. For measuring well-being, standardized tools like the Maslach Burnout Inventory (for measuring burnout), Patient Health Questionnaire-9 (depression), General Health Questionnaire-12 or 30 (psychological distress) and Perceived Stress Scale (stress) were used multiple times. For educational environment and work condition and environment, there is a lack of widely used tools for interns that have undergone psychometric testing in this population other than the Postgraduate Hospital Educational Environment Measure, which has been used in four different countries. Conclusions There are a large number of tools designed for measuring medical internship experience. International comparability of results from future studies would benefit if tools that have been more widely used are employed in studies on medical interns with further testing of their psychometric properties in different contexts.